Pernicious polarization, autocratization and opposition strategies. Issue 5 (4th July 2021) - Somer, Murat; McCoy, Jennifer L.; Luke, Russell E.
ABSTRACT: "Pernicious polarization" – the division of society into mutually distrustful Us versus Them camps in which political identity becomes a social identity – fosters autocratization by incentivizing citizens and political actors alike to endorse non-democratic action. An exploratory analysis of new V-Dem data on polarization indeed shows the negative relationship between the level of political polarization and liberal democracy ratings. How can pernicious polarization be avoided or reversed once present? By drawing on an endogenous explanation of polarization, where the decisions and actions of both opposition actors and incumbents contribute to its evolution, we focus on the question of what democratic opposition actors can do to stop or reverse pernicious polarization. Based on insights from examples across the world and deductive theory-building, along with illustrative cases, we offer a typology of potential opposition goals, strategies and tools, and then analyse how these may affect polarization and in turn democratic quality at early and late stages. We identify goals as either generative or preservative, and we argue that "active-depolarizing" and "transformative-repolarizing" strategies are more promising than "passive-depolarizing" and "reciprocal polarizing" strategies to improve a country's resilience to autocratizing pressures. The specific tools employed to pursue these goals and strategies are also crucial, though the effectiveness of available institutional accountability and mobilizational tools will change as the process of polarization advances. The emerging literatıres on opposition strategies to democratize electoral autocracies and to improve the resilience of democracies should incorporate their impact on polarization as a critical intervening variable.